2017
DOI: 10.4209/aaqr.2016.03.0110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Particulate Matter Regional Transport in Beijing Based on Numerical Simulation

Abstract: The frequent occurrence of regional air pollution makes it challenging to control. Based on source sensitivity research performed with the Chinese Unified Atmospheric Chemistry Environment (CUACE) model and dispersion simulation performed with the Flexible Particle dispersion model (FLEXPART), the regional transport of particulate matter (PM), potential source regions, and transport pathways were investigated for Beijing in summer (July) and winter (December) 2013. The mean near-surface trans-boundary contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Secondly, in the presence of high soil moisture, strong surface evaporation could increase the nearsurface RH, which is conducive to the hygroscopic growth of participles for haze formation (Dawson et al, 2014;. Additionally, high air temperature and strong solar radiation could enhance chemical conversions for the formation of secondary aerosols in the atmosphere (He et al, 2012;Huang et al, 2014). Furthermore, precipitation could impact the emissions of fugitive dust and depositions of air pollutants (Dawson et al, 2007;Cheng et al, 2016).…”
Section: Estimating the Contribution Of Regional Transport Of Pm 25 mentioning
confidence: 99%
“…Secondly, in the presence of high soil moisture, strong surface evaporation could increase the nearsurface RH, which is conducive to the hygroscopic growth of participles for haze formation (Dawson et al, 2014;. Additionally, high air temperature and strong solar radiation could enhance chemical conversions for the formation of secondary aerosols in the atmosphere (He et al, 2012;Huang et al, 2014). Furthermore, precipitation could impact the emissions of fugitive dust and depositions of air pollutants (Dawson et al, 2007;Cheng et al, 2016).…”
Section: Estimating the Contribution Of Regional Transport Of Pm 25 mentioning
confidence: 99%
“…In addition, dust particles carried away by winds from arid regions to the sampling location during this season could be the other reason. He et al (2017) have reported relationship between PM and wind through regional transport at Beijing.…”
Section: Meteorological Impact On Pmmentioning
confidence: 99%
“…Although the organic matter (OM) and FS mass concentrations increased, their relative contribution to PM 2.5 decreased slightly by 17% and 2%, respectively. The sharply increase in PM 2.5 from clean to light-medium pollution could be attributable to the regional transport of polluted air mass from the south (Li et al, 2016 b;He et al, 2017;Ma et al, 2017).…”
Section: Trajectory Clusteringmentioning
confidence: 99%